Self-Organization Process of Aluminum Oxide during Hard Anodization. (20th September 2016) - Li, Juan; Zhang, Zhiying; Li, Yuxin; Ma, Yingjun; Chen, Lin; Zhang, Zhongyue; Sun, Runguang
Graphical abstract: Abstract: The self-organization process of the porous anodic alumina (PAA) during hard anodization (HA) was proposed by synthetically investigating the nanopore morphology, the current density and barrier layer evolution of the PAA films, which were anodized in 0.3 M oxalic acid at 150 V (the voltage rising from 40 V to 150 V at the beginning). It was found that the high enough current density in the voltage rising stage can induce the fast film growth, which caused the pores to rapidly enlarge themselves and to reach a relatively ordered rearrangement. The barrier layer thickness showed linearly increase in voltage rising stage and then increased with a decelerated speed in the followed constant anodization stage, where the pores with growth advantage moved down straightly and gradually expanded their cell size to replace the inferior pores around. Accordingly, HA is a unequilibrium process and can be divided into two stages: I, the rapid pore enlargement and rearrangement during voltage rising stage, where the oxidation rate is larger than that of dissolution; II, competing growth of the nanopores during the followed constant voltage anodization, where the oxidation and dissolution rates approach to each other due to the thickened barrier layer. These findings are very helpful for more efficiently controlling the hard anodization process and developing new electrolyte systems to further broaden the interpore distance range.